Conservation and Energy Efficiency to Achieve the Comfort of The Air Conditioning System in The LTSIT Building, University of Lampung - Achmad Dzakwan; Dekpride Despa; Yulmartin Yulmartin; Dwi Asmi (Universitas Lampung, 2021)
This research was conducted in the context of conservation and energy efficiency to get the comfort of an ideal air conditioning system in the Integrated Laboratory of the Center for Technology Innovation, University of Lampung (LTSIT Unila). This situation is achieved by comparing the temperature of the existing air conditioning system with the SNI standard temperature. This energy conservation also aims to ensure the continuity of the activities of building users and working tools that remain within the Standard. On the other hand, there will be convenience for all building users, including in chemistry practicum. The method in this research is descriptive, data collection using survey methods to obtain facts that occur in the field and interpret the data. The results of this study indicate that the variables owned by the environment in the LTSIT building are at the lower limit of the ideal variables standardized by SNI. The initial temperature is at intervals with concertfasi and variable energy efficiency of the environmental system in the LTSIT building can be returned to a comfortable environment variable, where the initial temperature is at the interval (24.4oC-28.1oC) and in the end, the air conditioning system is obtained with room temperature 25oC.Keywords: Conservation, Efficiency, Comfort and SNI